The Most Memorable Characteristics In 20 Famous Logo Designs Among Design Students - Anwar Fikri , Abdullah; Muhamad Abdul Aziz , Ab. Gani (2014)
The purpose of this paper is to identify the memorable characteristics that appear in some famous logo designs that will be compiled as logo characteristic that are easily to remembered. Logo is used and believed as one of the very significant medium for the introduction of a brand and should be remembered. Gerber (2010) said; one of the important criteria should be considered before logo is been designed is how long it will be remembered. Start with the logo that people will remember then it will become famous; this is approved by Henderson & Cote (1998).The research is using pictorial survey study. The pictorial used is a partial design of the famous logos that have been crop using a simple 2 x 2 matrixes puzzle. The logos are purposely and properly crop into partial design that rids-off the original design. The results that have been captured showed positively that every famous logo come with specific characteristic that make it easily recognizable although it’s not been fully exposed. Therefore, this study starts with 20 famous logos among design students. The result can be acquired for reference by industry for commercial use. This study also directly contributes to the improvement of knowledge, especially in graphic design logo